1q21 gain but not t(4;14) indicates inferior outcomes in multiple myeloma treated with bortezomib. Issue 5 (15th April 2020) - Du, Chenxing; Mao, Xuehan; Xu, Yan; Yan, Yuting; Yuan, Chenglu; Du, Xin; Liu, Jiahui; Fan, Huishou; Wang, Qi; Sui, Weiwei; Deng, Shuhui; Fu, Mingwei; et al.
Abstract: Chromosome 1q21 aberrations in multiple myeloma have attracted much attention for a long time, however, the prognostic value is still under investigation. We confirmed the independent prognostic impact of 1q21 aberrations in this non-randomized clinical study. Our study noted that additional copies and larger clonal size of 1q21 gain did not worsen the outcome. We discovered that 1q21 gain was associated with the acquisition of new chromosome abnormalities and genomic instability, evidenced by the strong correlation between 1q21 gain and complex karyotypes or the acquisition of more than two cytogenetic aberrations. Moreover, 1q21 gain and/or del(17p) were powerful enough to discriminate high-risk patients. Furthermore, 1q21 gain retained unfavorable even when stratified by concurrent presence of t(4;14), especially in the bortezomib arm. Finally, although bortezomib might benefit patients with 1q21 gain, it could not completely overcome its adverse effects, suggesting the necessity of more effective therapies for these patients.